Multi-Omics insights into the molecular mechanisms of trochlear dysplasia: A proteomic and metabolomic study in rats - Zhenhui Huo; Huijun Kang; Peishuo Liu; Yanshuo Li; Yingzhen Niu; Kuo Hao; Chongyi Fan; Fei Wang; Wei Lin (PLoS ONE, 2025)
Introduction Trochlear dysplasia (TD) is a skeletal deformity that causes abnormal morphology of the trochlear groove, leading to patellar instability and related joint issues. Despite its clinical importance, the molecular mechanisms behind TD are not well understood. This study aims to explore these mechanisms using an integrated proteomic and metabolomic approach in a rat model of TD. Methods A rat model was developed by inducing a flat trochlear groove and increasing the sulcus angle. Validation was performed using gross morphology and micro-CT. Subchondral bone loss was evaluated through micro-CT. Non-targeted metabolomics was applied to identify differential metabolites, and proteomics was conducted to identify altered proteins. Pathway enrichment and interaction analyses were used to interpret the data. Results The TD rat model exhibited significant morphological and bone density changes, including notable subchondral bone loss. Metabolomic analysis identified 52 differentially expressed metabolites, with creatine and L-malic acid prominently altered. Proteomic analysis revealed 204 differentially expressed proteins. KEGG analysis highlighted critical pathways such as glycine, serine, and threonine metabolism and the PI3K-Akt signaling pathway. Integrative analysis showed correlations between key metabolites and proteins, providing deeper insights into TD-related molecular changes. Conclusions This study integrates proteomic and metabolomic analyses to uncover molecular alterations in a rat model of TD. Significant findings include upregulation of Col3a1 and altered metabolites such as creatine and L-malic acid. These results highlight the role of metabolic disturbances such as glycine, serine, and threonine metabolism and the PI3K-Akt signaling pathway in TD pathology. The study provides valuable biomarkers and insights into the mechanisms of TD, offering potential targets for future therapeutic and diagnostic strategies.